A normative study of levels of uranium in the urine of British Forces personnel. Issue 6 (12th October 2007) - Miller, B G; Colvin, A P; Hutchison, P A; Tait, H; Dempsey, S; Lewis, D; Soutar, C A
Abstract : Objectives: The UK Ministry of Defence (MoD) controls a biological monitoring programme that includes testing for uranium in personnel who served in the conflict in Iraq in 2003. To help interpret the results, the MoD commissioned this study to quantify a normative reference distribution of urinary uranium concentrations in military personnel who had not served in that conflict. Methods: The study selected and visited various military establishments to recruit a representative mix of ranks, genders and occupational groups (combat, support and auxiliary). A standardised protocol and recruitment questionnaire were used. The 125 ml spot urine samples collected were analysed for uranium and creatinine concentrations and (where possible) for uranium isotope 238 U/ 235 U ratio. Results: Samples from 732 eligible subjects were analysed. Adjusted uranium concentrations ranged up to 556 ng.g −1 creatinine, somewhat higher than reference values quoted for the USA but much lower than recorded in granite areas such as Finland. Isotope ratio measurements were available for 125 samples (17) with the highest concentrations; these all had a natural isotope signature and no evidence of depleted uranium (DU). On average, urinary uranium concentrations were somewhat lower in officers than in other ranks; they differed also across the services, the Navy being lowest and the Army highest. The levels give no concern regarding health risks in the personnel studied. Conclusion: Since even the highest values were from natural sources, we assume the differences represent differences in ingestion of natural uranium. Definition of a reference distribution or normal values will depend on the subpopulation of interest.